2006
DOI: 10.1002/ijc.21643
|View full text |Cite
|
Sign up to set email alerts
|

Definition of an HPV18/45 cross‐reactive human T‐cell epitope after DNA immunisation of HLA‐A2/KB transgenic mice

Abstract: Although human papillomavirus (HPV) types 16 and 18 are the most common types associated with cervical cancer worldwide, other related HPV types such as HPV 35, 45 and 58 have significant prevalence in geographically distinct populations. For development of global prophylactic and therapeutic vaccine strategies, it is important to study immune responses against these viruses and to define the degree of cross-reactivity between related HPV types. To investigate the potential for T cell cross-reactivity after va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The homology of E6 and E7 proteins within each class suggest the possibility that a broad coverage may be achieved by using a HPV 16 or HPV18 vaccine. In fact, a shared T cell epitope (KCIDFYSRI) that bound to HLA-A*0201 but not D b or K b molecules between HPV 18 and 45 was identified (31). In order to maximize potential immune cross-reactivity, especially at the T-cell level, we generated a HPV 18 consensus E6 and E7 DNA immunogen.…”
Section: Discussionmentioning
confidence: 99%
“…The homology of E6 and E7 proteins within each class suggest the possibility that a broad coverage may be achieved by using a HPV 16 or HPV18 vaccine. In fact, a shared T cell epitope (KCIDFYSRI) that bound to HLA-A*0201 but not D b or K b molecules between HPV 18 and 45 was identified (31). In order to maximize potential immune cross-reactivity, especially at the T-cell level, we generated a HPV 18 consensus E6 and E7 DNA immunogen.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the HPV18-E6 antigenic epitope characterized in this study, HPV18-E6aa67-75, has been evaluated by McCarthy et al and was suggested to be presented via HLA-A2 MHC molecules [17]. In their study, McCarthy et al .…”
Section: Discussionmentioning
confidence: 94%
“…While the MHC class I restriction of HPV18-E6aa67-75 epitope in naïve C57BL/6 mice has not been previously explored, an earlier publication evaluated the MHC class I restriction of this epitope in HLA-A2/KB transgenic mice and determined that this peptide sequence binds mainly to HLA-A2 [17]. We demonstrated that pcDNA3-HPV-18-E6 vaccination generated E6aa67-75 epitope-specific CD8+ T cell response in naïve C57BL/6 mice (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of their HLA-A2 binding, only these 4 Bax peptides would be predicted to be candidate T-cell epitopes. However, we included all the candidate HLA-A2 peptides in subsequent experiments because we have previously shown that even peptides with poor or low binding in the T2 assay can be T-cell epitopes (16,20).…”
Section: Peptide-binding Assaymentioning
confidence: 99%